Virulence and mutations analysis based on the whole genome of a Brazilian Corynebacterium diphtheriae strain isolated from a cutaneous infection - Araújo, Max Roberto Batista; Santos, Louisy Sanches dos; Prates, Fernanda Diniz; Perini, Hugo Felix; Silva, Jailan Sousa; Ramos, Juliana Nunes; Bokermann, Sérgio; Sacchi, Cláudio Tavares; Mattos Guaraldi, Ana Luíza de; Campos, Karoline Rodrigues; Cardoso, Tayná do Carmo Sant’Anna; Castro, Diogo Luiz de Carvalho; et al. (Frontiers in Microbiology, 2025)
Corynebacterium diphtheriae is the main etiological agent of diphtheria, a potentially fatal disease whose most severe signs and symptoms result from the action of an exotoxin, the diphtheria toxin (DT). Although non-toxigenic C. diphtheriae strains have been associated with several diseases, including cutaneous infections and endocarditis, they are not monitored in many countries, and their mechanisms of virulence and antimicrobial resistance remain underexplored. Therefore, this study aimed to provide a comprehensive characterization -through genomic, in vitro, and in vivo analyses - of a non-toxigenic C. diphtheriae strain (46855) isolated from a leg lesion, highlighting its pathogenic potential and resistance profile. The isolate was assigned to a novel sequence type (ST-925) and was found to be resistant to tetracycline and rifampin. Multiple antimicrobial resistance genes were predicted in the genome, such as tet(33), rbpA, and rpoB2, in addition to mutations in the rpoB gene. A diverse set of virulence-associated genes related to adhesion, iron uptake systems, gene regulation, and post-translational modification was also identified. The isolate was able to form biofilm in vitro and exhibited strong virulence in Galleria mellonella larvae and A549 human pneumocyte cells. Finally, the structural analysis of the rpoB gene, carried out for the first time in this study, linked the observed mutations to rifampin resistance in C. diphtheriae. In summary, the data revealed that C. diphtheriae 46855, although non-toxigenic, harbors multiple genes associated with antimicrobial resistance and virulence, emphasizing the need for greater surveillance and functional studies on non-toxigenic strains.